STEM-CP Based Flipped Classroom Model for HOTS of Prospective Elementary School Teacher - Dini Ramadhani; Ary Kiswanto Kenedi; Muhammad Febri Rafli; Hanif Harahap; Nadhira Azra Khalil (Universitas Pendidikan Ganesha, 2024)
This research was motivated by the development of a valid and feasible STEM-CP-based flipped classroom model to improve the Higher Order Thinking Skills (HOTS) of prospective elementary school teacher students. Further research is needed to determine the impact on HOTS of elementary school teacher candidates. The purpose of this study was to analyze the effect of the STEM-CP-based flipped classroom model on the HOTS of prospective teacher students. This research is quasi-experimental research with research subjects as many as 200 prospective teacher students. The research instrument used is a higher-order thinking test. Data were collected through administering tests to research subjects. Data analysis techniques are carried out with prerequisite tests, hypothesis tests, and further tests using the help of SPSS 26. The results showed that there was an influence of the STEM-CP-based flipped classroom model in increasing the HOTS of prospective elementary school teacher students. This study concluded that the STEM-CP-based flipped classroom model has a positive influence in improving the Higher Order Thinking Skills (HOTS) of elementary school teacher candidates. The implications of this research can be used as a reference for academics to improve the HOTS of prospective teacher students.